Battery
By adding fluorinated carbonates and silicamides to lithium-ion batteries, a stable SEI film is formed, which solves the problem of SEI film breakage caused by volume expansion during cycling in silicon-based batteries, and improves the high-temperature storage and cycle performance of the battery.
Patent Information
- Application Number
- CN202510751829.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-10-21
AI Technical Summary
During the cycle of silicon-based lithium-ion batteries, the SEI film is continuously broken and reorganized due to the volume expansion effect, resulting in loss of active lithium, worsening the battery cycle capacity retention rate, and intensifying battery side reactions at high temperatures, increasing the risk of gas production.
By adding fluorocarbonate and silamide additives to the electrolyte, a LiF-rich SEI film is formed, which captures the HF byproducts of the fluorocarbonate additives. The specific surface area of the pure silicon particles and the additive content are controlled to achieve a synergistic effect and reduce the side reactions between the electrolyte and the silicon particles.
It improves the cycle performance and high-temperature storage performance of silicon-based batteries, reduces the risk of gas generation in batteries, and enhances battery stability and lifespan.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a battery. Background Art
[0002] Secondary batteries, such as lithium-ion batteries, are widely used in digital electronics, energy storage, drones, power tools, and electric vehicles due to their high energy density, long cycle life, high safety, and fast charging capabilities. Silicon, as a negative electrode active material, offers a higher specific capacity than graphite, making it a preferred negative electrode material for next-generation batteries. However, during battery cycling, the volume expansion effect of silicon negative electrode materials causes the SEI film to continuously break up and reform, further leading to active lithium loss, deteriorating battery cycle capacity retention, and exacerbating battery side reactions at high temperatures, increasing the risk of gassing.
[0003] Based on this, there is an urgent need to provide a lithium-ion battery to improve the cycle and high-temperature storage performance of silicon-based batteries. Summary of the Invention
[0004] In order to solve the problems that existing silicon-based batteries have poor cycle performance and are prone to flatulence during high-temperature storage, the present invention provides a battery.
[0005] The technical solutions adopted by the present invention to solve the above technical problems are as follows: In a first aspect, the present invention provides a battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode comprises a negative electrode active material, the negative electrode active material comprises pure silicon particles, and the electrolyte comprises a fluorocarbonate additive and a silicon-based amide additive; The mass percentage of the fluorocarbonate additive in the electrolyte is A%; The mass percentage of the silicon-based amide additive in the electrolyte is B%; The specific surface area of the pure silicon particles is X m 2 / g; The battery satisfies Formula 1: 1.6≤(A+B) / X≤56 Formula 1.
[0006] Optionally, the battery satisfies Formula 2: 3.6≤(A+B) / X≤28 Formula 2.
[0007] Optionally, the mass percentage A% of the fluorocarbonate additive in the electrolyte is 5% to 40%; And / or, the mass percentage B% of the silicon-based amide additive in the electrolyte is 0.5% to 5%; And / or, the specific surface area of the pure silicon particles is 0.5 to 10 m 2 / g.
[0008] Optionally, the mass percentage A% of the fluorocarbonate additive in the electrolyte is 15% to 35%; And / or, the mass percentage B% of the silicon-based amide additive in the electrolyte is 1% to 4%; And / or, the specific surface area of the pure silicon particles is 1 to 6 m 2 / g.
[0009] Optionally, the battery satisfies Formula 3: 0.02≤B / A≤1 Formula 3; wherein, 5≤A≤40, 0.05≤B≤5.
[0010] Optionally, the fluorocarbonate additive includes at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, and 4-trifluoromethylethylene carbonate; And / or, the silicon-based amide additive includes at least one of N,O-bis(trimethylsilyl)acetamide, N,O-bis(trimethylsilyl)trifluoroacetamide, N,O-bis(tert-butyldimethylsilyl)acetamide, N-(trimethylsilyl)acetamide, N,O-bis(diethylsilyl)trifluoroacetamide, N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide, and N-methyl-N-(trimethylsilyl)acetamide.
[0011] Optionally, the electrolyte further includes auxiliary additives, and the auxiliary additives include at least one of succinonitrile, adiponitrile, ethylene glycol dipropylene glycol ether, 1,3,6-hexanetrinitrile, glycerol trinitrile, 1,3-propane sultone, propenyl-1,3-sultone, vinyl sulfate, methylene disulfonate, lithium difluorophosphate, lithium tetrafluoroborate, and lithium difluorooxalatoborate.
[0012] Optionally, the mass content of the auxiliary additive in the electrolyte is 1% to 15%.
[0013] Optionally, the negative electrode active material is selected from pure silicon particles.
[0014] Optionally, the positive electrode includes a positive electrode active material, and the positive electrode active material includes one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganate, lithium manganese iron phosphate, and lithium vanadium phosphate; the chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0015] In the present invention, the size of the specific surface area of the silicon particles directly affects the contact between the electrolyte and the electrode interface. By introducing fluorocarbonate additives, a SEI film rich in LiF components is formed on the surface of the silicon particles, thereby improving the interface stability of the silicon particles. By introducing silicon-based amide additives, the HF byproducts of the decomposition of fluorocarbonate additives at high temperatures are captured, thereby improving the storage gas production. At the same time, the silicon-based structure of the silicon-based amide additive has strong reducing properties, and a stable SEI film can be formed on the surface of the silicon particles, which has good compatibility with the silicon particles. In particular, by regulating the specific surface area of pure silicon particles, the content of fluorocarbonate additives, and the content of silicon-based amide additives, so that they meet 1.6≤(A+B) / X≤56, the specific surface area of the silicon particles, the fluorocarbonate additives, and the silicon-based amide additives can play a better synergistic role, further reducing the side reactions between the electrolyte and the silicon particles, and improving the cycle and high-temperature storage performance of the silicon-based battery. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0017] One embodiment of the present invention provides a battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode comprises a negative electrode active material, the negative electrode active material comprises pure silicon particles, and the electrolyte comprises a fluorocarbonate additive and a silicon-based amide additive; The mass percentage of the fluorocarbonate additive in the electrolyte is A%; The mass percentage of the silicon-based amide additive in the electrolyte is B%; The specific surface area of the pure silicon particles is X m 2 / g; The battery satisfies Formula 1: 1.6≤(A+B) / X≤56 Formula 1.
[0018] In this embodiment, the specific surface area of the silicon particles directly affects the contact between the electrolyte and the electrode interface. A larger specific surface area increases the chances of electrolyte-electrode interface contact, which is beneficial for ion transport. However, a larger specific surface area also increases the number of interfacial side reactions. A smaller specific surface area reduces the chances of electrolyte-electrode interface contact, obstructing the ion transport path and detrimental to battery cycle performance.
[0019] By introducing fluorocarbonate additives, a LiF-rich SEI film is formed on the surface of silicon particles, improving the interfacial stability of silicon particles. However, fluorocarbonate additives are prone to decomposition and gasification at high temperatures. At the same time, when their content is high, the viscosity of the electrolyte increases, deteriorating the battery cycle performance.
[0020] By introducing silicon-based amide additives to capture the HF byproducts of the decomposition of fluorocarbonate additives at high temperatures, storage gas production is improved. At the same time, the silicon-based structure of the silicon-based amide additives has strong reducing properties, which can form a stable SEI film on the surface of silicon particles and has good compatibility with silicon particles. However, when the content of silicon-based amide additives is too high, the increase in electrolyte viscosity will also deteriorate the cycle performance. In particular, this embodiment regulates the specific surface area of pure silicon particles, the content of fluorocarbonate additives, and the content of silicon-based amide additives so that they meet 1.6≤(A+B) / X≤56. The specific surface area of silicon particles, fluorocarbonate additives, and silicon-based amide additives can play a better synergistic role, further reducing the side reactions between the electrolyte and silicon particles, and improving the cycle and high-temperature storage performance of silicon-based batteries. When (A+B) / X is less than 1.6, the total amount of additives is relatively small, or the specific surface area of silicon is relatively large, and the additives are insufficient to form a stable and sufficient interface film at the contact interface between the electrolyte and the electrode to inhibit the occurrence of interface side reactions, resulting in a significant deterioration in the high-temperature storage and cycle performance of the battery. When (A+B) / X is greater than 56, the additive content is relatively high, or the silicon surface area is relatively small, resulting in increased electrolyte viscosity and increased interfacial impedance. A silicon surface area that is too small reduces the contact opportunities for lithium ions at the electrode interface, deteriorating lithium ion transport across the electrode interface and leading to poor cycling performance.
[0021] In a preferred embodiment, the battery satisfies Formula 2: 3.6≤(A+B) / X≤28 Formula 2. When the specific surface area of pure silicon particles, the content of fluorocarbonate additives, and the content of silicon-based amide additives satisfy the above relationship, the cycling and high-temperature storage performance of the silicon-based battery can be further improved.
[0022] In some embodiments, the mass percentage A% of the fluorocarbonate additive in the electrolyte is 5% to 40%. By regulating the content of the fluorocarbonate additive within the above range, the interfacial stability of the silicon particles is improved, and the cycle and high-temperature storage performance of the silicon-based battery is improved. When the content of the fluorocarbonate additive is less than 5% or greater than 40%, the cycle performance is poor. When the content of the fluorocarbonate additive is less than 5%, the protection of the electrode interface is insufficient, the side reaction between the electrolyte solvent and the silicon negative electrode surface is aggravated, and the cycle performance is deteriorated. When the content of the fluorocarbonate additive is greater than 40%, the viscosity of the electrolyte increases, the transmission of lithium ions is hindered, and the interface impedance is increased. At the same time, when the content of the fluorocarbonate additive is high, it is easy to decompose and generate HF, which corrodes the active material and deteriorates the cycle performance. At the same time, when the content of the fluorocarbonate additive is greater than 40%, the storage deteriorates sharply.
[0023] Specifically, the content of the fluorocarbonate additive includes but is not limited to 5%, 8%, 11%, 14%, 17%, 20%, 23%, 26%, 29%, 32%, 35%, 38% or 40%.
[0024] In a preferred embodiment, the mass percentage A% of the fluorocarbonate additive in the electrolyte is 15% to 35%. By regulating the content of the fluorocarbonate additive within this range, the interfacial stability of the silicon particles is further improved, thereby enhancing the cycling and high-temperature storage performance of silicon-based batteries.
[0025] In some embodiments, the mass percentage B% of the silicon-based amide additive in the electrolyte is 0.5% to 5%. By regulating the content of the silicon-based amide additive within the above range, the gas generation problem of the fluorocarbonate additive at high temperature is improved, and a stable SEI film is formed on the surface of the silicon particles, thereby improving the cycle and high-temperature storage performance of the silicon-based battery. When the content of the silicon-based amide additive is less than 0.5%, it is not enough to improve the high-temperature storage performance. When the content of the silicon-based amide additive is greater than 5%, the storage performance is relatively good. However, due to the high content of the silicon-based amide additive, the viscosity of the electrolyte increases, the interfacial impedance increases, and the cycle performance deteriorates.
[0026] Silicon-based amide additives include, but are not limited to, 0.5%, 0.8%, 1.1%, 1.4%, 1.7%, 2.0%, 2.3%, 2.6%, 2.9%, 3.2%, 3.5%, 3.8%, 4.0%, 4.3%, 4.6% or 5%.
[0027] In a preferred embodiment, the mass percentage B% of the silicon-based amide additive in the electrolyte is 1% to 4%. By adjusting the content of the silicon-based amide additive within the above range, the cycling and high-temperature storage performance of the silicon-based battery can be further improved.
[0028] In some embodiments, the specific surface area of the pure silicon particles is 0.5 to 10 m 2 By regulating the specific surface area of pure silicon particles within the above range, the ion transport performance is guaranteed, while the interface side reactions are suppressed, thereby improving the high-temperature storage and cycle performance of the battery.
[0029] When the specific surface area of silicon particles is less than 0.5 m 2 / g, the contact opportunity between the electrode interface and the electrolyte is greatly reduced, the interface side reaction is reduced, and the storage performance is improved, but the ion transmission is hindered, which deteriorates the battery cycle performance. 2 / g, the contact opportunities between the electrolyte and the electrode interface increase, the side reactions intensify, the high-temperature storage and high-temperature cycling deteriorate significantly, and the low-temperature cycling also deteriorates slightly.
[0030] Specifically, the specific surface area of pure silicon particles includes but is not limited to 0.5 m 2 / g, 0.9 m 2 / g, 1.3 m 2 / g, 1.7m 2 / g, 2.1 m 2 / g, 2.5 m 2 / g, 2.9 m 2 / g, 3.3 m 2 / g, 3.7 m 2 / g, 4.1 m 2 / g, 4.5 m 2 / g, 4.9 m 2 / g, 5.1 m 2 / g, 5.5 m 2 / g, 5.9 m 2 / g, 6.3 m 2 / g, 6.7 m 2 / g, 8.1 m 2 / g, 8.5 m 2 / g, 8.9 m 2 / g, 9.3 m 2 / g, 9.7 m 2 / g or 10m 2 / g.
[0031] In a preferred embodiment, the specific surface area of the pure silicon particles is 1 to 6 m 2 / g.
[0032] In some embodiments, the battery satisfies Equation 3: 0.02≤B / A≤1 (Equation 3); wherein, 5≤A≤40, and 0.05≤B≤5. By regulating the content relationship of the fluorocarbonate additive and the silicon-based amide additive to satisfy the above relationship, the silicon-based amide additive can capture the decomposition products of the fluorocarbonate additive at high temperatures, thereby improving storage gas production. When B / A is less than 0.02, that is, when the content of the silicon-based amide additive is too low, or when the content of the fluorocarbonate additive is too high, the silicon-based amide additive is not significantly effective in suppressing the gas production of the fluorocarbonate additive, and high-temperature storage gas production is significantly deteriorated. When the battery satisfies both Equations 1 and 3, side reactions between the electrolyte and the silicon material can be further reduced, improving the cycling and high-temperature storage performance of the silicon-based battery. When B / A is greater than 1, the electrolyte viscosity increases, deteriorating the battery's cycling performance.
[0033] In some embodiments, the fluorocarbonate additive includes at least one of fluoroethylene carbonate (CAS No. 114435-02-8), bisfluoroethylene carbonate (CAS No. 171730-81-7), and 4-trifluoromethylethylene carbonate (CAS No. 167951-80-6). The use of these fluorocarbonate additives facilitates the formation of a LiF-rich SEI film on the surface of the silicon particles.
[0034] In some embodiments, the silicon-based amide additive includes at least one of N,O-bis(trimethylsilyl)acetamide (CAS No.: 10416-59-8), N,O-bis(trimethylsilyl)trifluoroacetamide (CAS No.: 25561-30-2), N,O-bis(tert-butyldimethylsilyl)acetamide (CAS No.: 82112-21-8), N-(trimethylsilyl)acetamide (CAS No.: 13435-12-6), N,O-bis(diethylsilyl)trifluoroacetamide (CAS No.: 105384-38-1), N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide (CAS No.: 77377-52-7), and N-methyl-N-(trimethylsilyl)acetamide (CAS No.: 7449-74-3). By selecting the above-mentioned silicon-based amide additives, the storage gas production is improved while forming a stable SEI film on the surface of the silicon particles.
[0035] In some embodiments, the electrolyte further includes auxiliary additives, including at least one of succinonitrile, adiponitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrionitrile (HTCN), glycerol trinitrile, 1,3-propane sultone (PS), propenyl-1,3-sultone, diethylene sulfate (DTD), methylene methanedisulfonate, lithium difluorophosphate, lithium tetrafluoroborate, and lithium difluorooxalatoborate. The addition of these auxiliary additives, in conjunction with fluorocarbonate additives and silicon-based amide additives, enhances the stability of the electrolyte and improves the storage and cycling performance of the battery.
[0036] In some embodiments, the auxiliary additive has a mass content of 1% to 15% in the electrolyte. By selecting auxiliary additives within the above content range, the stability of the electrolyte is further improved. Specifically, the mass content of the auxiliary additive includes but is not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5% or 15%.
[0037] In some embodiments, the negative electrode active material is selected from pure silicon particles. Specifically, the negative electrode active material is pure silicon particles with different specific surface areas.
[0038] In some embodiments, the electrolyte further includes a solvent, and the solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methylpropyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, methyl acetate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether. By selecting the above solvents, the viscosity of the electrolyte is within an appropriate range.
[0039] In some embodiments, the electrolyte further includes a lithium salt, and the concentration of the lithium salt in the electrolyte is 0.8 to 1.5 M. The lithium salt includes, but is not limited to, at least one of lithium hexafluorophosphate LiPF6, lithium perchlorate LiClO4, lithium tetrafluoroborate LiBF4, lithium hexafluoroarsenate LiAsF6, and other organic lithium salts (e.g., lithium trifluoromethanesulfonate LiCF3SO, lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, lithium trifluoromethylsulfonyl-perfluorobutylsulfonylimide LiTNFSI, lithium fluorosulfonyl-perfluorobutylsulfonylimide LiFNFSI, lithium bis(oxalatoborate) LiBOB, LiN(CF3SO2)2, and LiC(SO2CF3)3).
[0040] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0041] In some embodiments, the positive electrode active material includes one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganate, lithium manganese iron phosphate, and lithium vanadium phosphate; the chemical formula of the transition metal lithium oxide is Li 1+ x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0042] In this embodiment, the type of positive electrode current collector is not particularly limited and can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes at least one or more of a metal material such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon cloth or carbon paper.
[0043] In a preferred embodiment, the positive electrode current collector is made of metal material.
[0044] In some embodiments, the positive electrode active material layer further includes a positive electrode conductor, a positive electrode binder, and a solvent.
[0045] In some embodiments, the types of the positive electrode conductor and positive electrode binder mentioned in the present invention are not limited, and any known conductor and binder can be used.
[0046] Specifically, the positive electrode conductor includes at least one of natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene. The positive electrode binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.
[0047] In the above embodiments, there is no particular limitation on the negative electrode current collector as long as the purpose of the present application can be achieved. For example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper or a composite current collector.
[0048] In some preferred embodiments, the negative electrode current collector is selected from copper foil.
[0049] In some embodiments, the negative electrode further includes a negative electrode active material layer, which is disposed on at least one side of the current collector. The negative electrode active material layer further includes a negative electrode conductor, a negative electrode binder, a thickener, and a solvent.
[0050] The negative electrode conductive agent includes at least one of natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene. The negative electrode binder includes styrene-butadiene latex, the thickener includes CMC, and the solvent includes deionized water.
[0051] In the lithium-ion battery mentioned in this application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. There is no particular limitation on the material and shape of the separator, as long as it does not significantly impair the effect of this application.
[0052] In some embodiments, the diaphragm comprises a porous sheet or non-woven fabric-like material with excellent liquid retention, and the diaphragm is selected from a resin or glass fiber diaphragm material, and the resin or glass fiber diaphragm material includes but is not limited to polyolefin, aromatic polyamide, polytetrafluoroethylene, and polyethersulfone.
[0053] In some embodiments, the lithium-ion battery further includes an outer packaging, which can be used to encapsulate the electrode assembly and the electrolyte.
[0054] In some embodiments, the outer packaging of the lithium-ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the lithium-ion battery can also be a soft package, such as a pouch-type soft package.
[0055] The material of the soft pack can be plastic, including but not limited to polypropylene, polybutylene terephthalate and polybutylene succinate. The present application has no particular limitation on the shape of the lithium-ion battery, which can be cylindrical, square or any other shape.
[0056] On the other hand, an embodiment of the present application provides an electrical device comprising the lithium-ion battery described above.
[0057] Exemplarily, the above-mentioned electrical devices may include but are not limited to mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, and energy storage systems.
[0058] The present invention is further described below with reference to the following examples.
[0059] Example 1 This embodiment is used to illustrate the battery disclosed in the present invention.
[0060] electrolyte Ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (EP) and diethyl carbonate (DEC) were mixed and stirred in a mass ratio of 10:20:40:30 to form a mixed solvent, and water was removed through a molecular sieve for standby use.
[0061] Additives and lithium salt LiFSI were added to the mixed solvent. The types and amounts of the additives were shown in Tables 1 and 2. The concentration of the lithium salt was 1 M to obtain an electrolyte.
[0062] Positive electrode The positive electrode active material lithium cobalt oxide, the positive electrode conductive agent acetylene black (SuperP) and the polyvinylidene fluoride (PVDF) binder are evenly mixed in a mass ratio of 97:1.5:1.5, and evenly dispersed with 1-methyl-2-pyrrolidone (NMP) to form a uniform positive electrode slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the positive electrode sheet.
[0063] Negative electrode The negative electrode active material, pure silicon particles, the negative electrode conductive agent, acetylene black (Super P), the thickener CMC, and the negative electrode binder SBR were mixed uniformly in a mass ratio of 94:2:1.2:2.8 and evenly dispersed in deionized water to form a uniform negative electrode slurry. The mixed slurry was coated on both sides of the copper foil current collector, baked, roll-pressed, and cut into pieces to obtain the negative electrode sheets. The specific surface area of the added pure silicon particles is shown in Table 1.
[0064] Battery production: The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets. After winding and welding the tabs, a bare core is obtained. The bare core is placed in an aluminum-plastic film, liquid is injected, and encapsulated to obtain a lithium-ion battery.
[0065] Examples 2 to 25 This embodiment is used to illustrate the battery disclosed in the present invention and includes most of the steps in Example 1, except that the formulation in Table 1 is used.
[0066] Examples 26 to 32 This embodiment is used to illustrate the battery disclosed in the present invention and includes most of the steps in Example 1, except that the formulation in Table 2 is used.
[0067] Comparative Examples 1 to 19 The comparative example is used to compare and illustrate the battery disclosed in the present invention, and includes most of the steps in Example 1, except that the formulation in Table 1 is used.
[0068] Comparative Example 20 Comparative Example 20 is used to compare and illustrate the battery disclosed in the present invention, and includes most of the steps in Example 1, except that the formula in Table 2 is used without adding auxiliary additives.
[0069] Table 1 Table 2 Performance Testing 1. The batteries prepared in the above examples and comparative examples were subjected to the following performance tests: 60℃ storage performance test The lithium-ion batteries prepared in the above embodiments and comparative examples were charged at a rate of 1C to a cutoff voltage and a cutoff current of 0.025C at 25°C, left to stand for 5 minutes, and the thickness H1 of the lithium-ion batteries was measured; they were then stored at 60°C for 60 days, and the thickness H2 of the lithium-ion batteries was measured after the storage.
[0070] Thickness expansion ratio = [(H2-H1) / H1] × 100%.
[0071] 0℃ cycle performance test The lithium-ion batteries prepared in the above embodiments and comparative examples were charge-discharge cycled at 0°C at a rate of 1C / 1C within the charge-discharge cut-off voltage range. The discharge capacity of the first cycle was measured as C1, and the discharge capacity of the 600th cycle was measured as C2. The capacity of the 600th cycle was divided by the capacity of the first cycle to obtain the cycle capacity retention rate R2 = C2 / C1 at the 600th cycle.
[0072] 45℃ cycle performance test The lithium-ion batteries prepared in the above embodiments and comparative examples were charge-discharge cycled at 45°C at a rate of 1C / 1C within the charge-discharge cut-off voltage range. The discharge capacity in the first cycle was measured as X1, and the discharge capacity in the 600th cycle was measured as X2. The capacity in the 600th cycle was divided by the capacity in the first cycle to obtain the cycle capacity retention rate in the 600th cycle, Y2 = X2 / X1.
[0073] The test results are shown in Table 3.
[0074] Table 3 It can be seen from the test results of Comparative Examples 1 and 2 in Table 3 that the storage performance deteriorates when fluorocarbonate additives are added. This is because fluorocarbonate additives are easily decomposed and gasified under high-temperature storage. The addition of fluorocarbonate additives can form a stable interface film at the electrode interface, thereby improving the cycle performance. It can be seen from the test results of Comparative Examples 4 and 5 and Example 3 that when the fluorocarbonate additive is less than 5% or greater than 40%, the cycle performance is poor. When the fluorocarbonate additive is less than 5%, the protection of the electrode interface is insufficient, the side reaction between the electrolyte solvent and the silicon negative electrode surface is aggravated, and the cycle performance is deteriorated. When the fluorocarbonate additive is greater than 40%, the viscosity of the electrolyte increases, lithium ion transmission is hindered, and the interface impedance is increased. At the same time, when the content of the fluorocarbonate additive is high, it is easy to decompose and generate HF, which corrodes the active material and deteriorates the cycle performance. When the content of the fluorocarbonate additive is greater than 40%, the storage deteriorates sharply. According to the test results of Examples 1-5, as the content of fluorocarbonate additives increases, the storage performance deteriorates. This is because fluorocarbonate additives are easily decomposed under high-temperature storage; as the content of fluorocarbonate additives increases, the cycle performance first improves and then deteriorates. The first improvement is because fluorocarbonate additives can form a stable interface protective film on the surface of the silicon negative electrode, inhibiting the side reaction between the electrolyte and the negative electrode interface. However, as the content of fluorocarbonate additives continues to increase, the viscosity of the electrolyte increases, the transmission of lithium ions is hindered, and the interface impedance increases. At the same time, when the content of fluorocarbonate additives is high, it will decompose to produce by-products such as HF, which aggravates the deterioration of the click interface.
[0075] According to the test results of Comparative Example 3, the battery storage performance is improved due to the addition of silicon-based amide additives. This is because the amide groups in the silicon-based amide compounds can remove water and acid, capture the HF by-products decomposed during high-temperature storage, and further inhibit the occurrence of gas production. With the addition of silicon-based amide additives, its silicon-based functional groups can stably form films on the surface of the silicon negative electrode, improve interfacial side reactions, and thus improve the cycle performance. It can be seen from the test results of Comparative Examples 6 and 7 and Example 3 that when the content of silicon-based amide additives is less than 0.5%, it is not enough to improve the high-temperature storage performance. When the content of silicon-based amide additives is greater than 10%, the storage performance is relatively good, but due to the high content of silicon-based amide additives, the viscosity of the electrolyte increases, the interface impedance increases, and the cycle performance deteriorates. The test results of Examples 6-10 and Example 3 show that as the content of the silicon-based amide additive increases, high-temperature storage improves. This is because the amide groups of the silicon-based amide additive can remove water and acid, inhibiting the decomposition and gas production of the fluorocarbonate additive. At the same time, the silicon-based group can form a stable SEI film on the silicon negative electrode side to improve cycle performance. As the content of the silicon-based amide additive increases, the cycle performance first improves and then deteriorates. When the content of the silicon-based amide additive is high, the viscosity of the electrolyte increases, and the interfacial impedance increases, which deteriorates the cycle performance.
[0076] The test results of Examples 16-19 and Example 3 show that when the fluorocarbonate additives are other carbonates or fluorinated compounds, the performance improvement is not as good as that of Example 3, further proving that the optimal synergistic effect can only be achieved when the fluorocarbonate additives and the silicon-based amide additives are used in combination. When the silicon-based amide additives are other amides or silicon-based compounds, the performance improvement is not as good as that of Example 3, further proving that the optimal synergistic effect can only be achieved when the fluorocarbonate additives and the silicon-based amide additives are used in combination.
[0077] It can be seen from the test results of Example 3 and Examples 26-32 that when there are no auxiliary additives, the storage and cycle performance of the battery deteriorate. The auxiliary additives can form an initial interface film at the electrode interface, making the chemical stability of the interface film better. When auxiliary additives are present, fluorocarbonate additives and silicon-based amide additives can achieve the best synergistic effect.
[0078] The test results of Examples 10-11 and 1-17 indicate that the B / A ratio (the ratio of the content of the silicon-based amide additive to the fluorocarbonate additive) is too low, either because the content of the silicon-based amide additive is too low or because the content of the fluorocarbonate additive is too high. Consequently, the silicon-based amide additive has little effect in suppressing the gas production of the fluorocarbonate additive. In other words, when the B / A ratio is less than 0.02, gas production during high-temperature storage is significantly deteriorated.
[0079] According to the test results of Comparative Examples 12-15 and Examples 1-17, the specific surface area of pure silicon particles, the content of fluorocarbonate additives, and the content of silicon-based amide additives all meet the following conditions: 1.6≤(A+B) / X≤56, 0.02≤B / A≤1, A% is 5%~40%, B% is 0.5%~5%, and X is 0.5~10 m 2 / g, the battery performance is best. When (A+B) / X is less than 1.6, it means that the total amount of additives is relatively small, or the specific surface area of silicon is relatively large, and the additives are not enough to form a stable and sufficient interface film at the interface to inhibit the occurrence of interface side reactions. And when (A+B) / X is less than 1.6, the high-temperature storage and cycle performance deteriorate significantly. When (A+B) / X is greater than 56, the additive content is relatively high, or the specific surface area of silicon is relatively small. More additives will lead to increased viscosity of the electrolyte and increased interface impedance. The specific surface area of silicon is too small, resulting in fewer opportunities for lithium ions to contact at the electrode interface, worsening the transmission of lithium ions at the electrode interface, and thus leading to deterioration of cycle performance.
[0080] The test results of Examples 18-25 show that when the fluorocarbonate additive and the silylamide additive are of the same type, the battery also exhibits good storage and cycle performance. The test results of Examples 26-32 show that when auxiliary additives are of other types and categories, they can also promote the synergistic effect of the fluorocarbonate additive and the silylamide additive.
[0081] It should be noted that the concentration of the lithium salt in this embodiment can be any concentration between 0.8M and 1.5M, and is not limited to 1M.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode active material, the negative electrode active material comprises pure silicon particles, and the electrolyte comprises a fluorocarbonate additive and a silicon-based amide additive; The mass percentage of the fluorocarbonate additive in the electrolyte is A%; The mass percentage of the silicon-based amide additive in the electrolyte is B%; The specific surface area of the pure silicon particles is X m 2 / g; The battery satisfies Formula 1: 1.6≤(A+B) / X≤56 Formula 1.
2. The battery according to claim 1, characterized in that The battery satisfies Formula 2: 3.6≤(A+B) / X≤28 Formula 2.
3. The battery according to claim 1, characterized in that The mass percentage A% of the fluorocarbonate additive in the electrolyte is 5% to 40%; And / or, the mass percentage B% of the silicon-based amide additive in the electrolyte is 0.5% to 5%; And / or, the specific surface area of the pure silicon particles is 0.5 to 10 m 2 / g.
4. The battery according to claim 3, characterized in that The mass percentage A% of the fluorocarbonate additive in the electrolyte is 15% to 35%; And / or, the mass percentage B% of the silicon-based amide additive in the electrolyte is 1% to 4%; And / or, the specific surface area of the pure silicon particles is 1 to 6 m 2 / g.
5. The battery according to claim 1, characterized in that The battery satisfies Formula 3: 0.02≤B / A≤1 Formula 3; wherein, 5≤A≤40, 0.05≤B≤5.
6. The battery according to claim 1, characterized in that The fluorocarbonate additive includes at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, and 4-trifluoromethylethylene carbonate; And / or, the silicon-based amide additive includes at least one of N,O-bis(trimethylsilyl)acetamide, N,O-bis(trimethylsilyl)trifluoroacetamide, N,O-bis(tert-butyldimethylsilyl)acetamide, N-(trimethylsilyl)acetamide, N,O-bis(diethylsilyl)trifluoroacetamide, N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide, and N-methyl-N-(trimethylsilyl)acetamide.
7. The battery according to claim 1, characterized in that The electrolyte further includes auxiliary additives, which include at least one of succinonitrile, adiponitrile, ethylene glycol dipropylene glycol ether, 1,3,6-hexanetrinitrile, glycerol trinitrile, 1,3-propane sultone, propenyl-1,3-sultone, vinyl sulfate, methylene methanedisulfonate, lithium difluorophosphate, lithium tetrafluoroborate, and lithium difluorooxalatoborate.
8. The battery according to claim 7, characterized in that The auxiliary additive has a mass content of 1% to 15% in the electrolyte.
9. The battery according to claim 1, characterized in that The negative electrode active material is selected from pure silicon particles.
10. The battery according to claim 1, characterized in that The positive electrode includes a positive electrode active material, and the positive electrode active material includes one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganate, lithium manganese iron phosphate, and lithium vanadium phosphate; the chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.